Detection of a contaminant cell culture line by restriction endonuclease cleavage patterns of mitochondrial DNA. - Grossman, L I (1977)
A putative HeLa cell culture line was discovered to be contaminated with mouse cells by examination of agarose gel profiles of restriction endonuclease digests of mitochondrial DNA. The contamination was confirmed by karyotypic analysis, and by observation of the mouse satellite band in an analytical buoyant density centrifugation of total cellular DNA. Restriction endonuclease analysis of mitochondrial DNA is suggested as a useful method for monitoring the species of cells in culture.